(110)‐Oriented ZIF‐8 Thin Films on ITO with Controllable Thickness1. Issue 1 (5th October 2012) - Hou, Chuantao; Xu, Qin; Peng, Jinyun; Ji, Zhengping; Hu, Xiaoya
Abstract (110)‐oriented zeolitic imidazolate framework (ZIF)‐8 thin films with controllable thickness are successfully deposited on indium tin oxide (ITO) electrodes at room temperature. The method applied uses 3‐aminopropyltriethoxysilane (APTES) in the form of self‐assembled monolayers (SAMs), followed by a subsequent adoption of the layer‐by‐layer (LBL) method. The crystallographic preferential orientation (CPO) index shows that the ZIF‐8 thin films are (110)‐oriented. A possible mechanism for the growth of the (110)‐oriented ZIF‐8 thin films on 3‐aminopropyltriethoxysilane modified ITO is proposed. The observed cross‐sectional scanning electron microscopy (SEM) images and photoluminescent (PL) spectra of the ZIF‐8 thin films indicate that the thickness of the ZIF‐8 layers is proportional to the number of growth cycles. The extension of such a SAM method for the fabrication of ZIF‐8 thin films as described herein should be applicable in other ZIF materials, and the as‐prepared ZIF‐8 thin films on ITO may be explored for photoelectrochemical applications.